2022
DOI: 10.1097/mnh.0000000000000832
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for risk stratification in kidney disease

Abstract: Purpose of reviewRisk stratification for chronic kidney is becoming increasingly important as a clinical tool for both treatment and prevention measures. The goal of this review is to identify how machine learning tools contribute and facilitate risk stratification in the clinical setting.Recent findingsThe two key machine learning paradigms to predictively stratify kidney disease risk are genomics-based and electronic health record based approaches. These methods can provide both quantitative information such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The minimum number of samples n such that E[g n (X train , X train )] < 1.0 is the minimum convergence sample estimate. Above the minimum convergence sample, our previous work has shown that the decrease in autoencoder loss is proportional to the gain in generalizability as measured by area-under-the-curve metric 4 . We have previously shown that the minimum convergence sample estimate remains a valid approximation of generalizability across model architecture, hyperparameter selections, dataset dimensions and dataset complexity.…”
Section: Methodsmentioning
confidence: 99%
“…The minimum number of samples n such that E[g n (X train , X train )] < 1.0 is the minimum convergence sample estimate. Above the minimum convergence sample, our previous work has shown that the decrease in autoencoder loss is proportional to the gain in generalizability as measured by area-under-the-curve metric 4 . We have previously shown that the minimum convergence sample estimate remains a valid approximation of generalizability across model architecture, hyperparameter selections, dataset dimensions and dataset complexity.…”
Section: Methodsmentioning
confidence: 99%
“…• Disease prediction and Risk Stratification: ML algorithms scrutinize genomic data to discern patterns and variations linked to specific diseases. This analytical approach allows for the assessment of the risk associated with certain health conditions [144]- [148].…”
Section: Genomic Datamentioning
confidence: 99%
“…The medical term for the slow, progressive loss of kidney function that occurs over time is "chronic." CKD is a leading cause of death in countries owing to a lack of access to quality, cost-effective healthcare [14]. CKD may lead to cardiovascular disease and is permanent in its progression.…”
Section: Introductionmentioning
confidence: 99%